O efeito do foco regulatório de promoção na escolha do consumidor - Sousa, Tereza Cristina Pereira dos Santos (Universidade Federal do Tocantins, 2020)
The purpose of this article is to evaluate the consumer choice decision and how the information is arranged influences the decision making. For the preparation of this study, the pioneer of Higgins' regulatory focus theory was used as a theoretical basis among other authors who emphasize the study of this theory, and the application of an electronic questionnaire to students of a public university. The results showed that the validity of the information related to the regulatory justification of the promotion individual with adjustment or without adjustment, influence the decision making of the consumer Keywords: Choose. Consumer. Promotion. Prevention. Regulatory Adjustment.